Permanent and seasonal human presence in the coastal settlements of Lecce: An analysis using mobile phone tracking data - Curci, Francesco; Kercuku, Agim; Zanfi, Federico; Novak, Christian (TeMA - Journal of Land Use, Mobility and Environment, 2022)
<span class="NormalTextRun SCXW209618213 BCX0" data-ccp-parastyle="Abstract" data-ccp-parastyle-defn="{"ObjectId":"00000000-0000-0000-0000-000000000000|0","ClassId":1073872969,"Properties":[469775450,"Abstract",201340122,"2",134234082,"true",134233614,"true",469778129,"Abstract",335572020,"1",469777841,"Tahoma",469777842,"Tahoma",469777844,"Tahoma",469769226,"Tahoma",268442635,"18",335551547,"1033",335559740,"276",201341983,"0",335559739,"0",335551550,"6",335551620,"6",469778324,"Normal"]}">This paper presents the first results of analyses carried out using mobile phone data on human presence (residents, commuters, visitors) in the coastal territory of Lecce (Italy). The aim of the research, conducted in the framework of the DASTU Project ‘Department of Excellence on Fragile Territories’ in collaboration with the Municipality of Lecce, is to provide precise feedback on the actual use of a coastal territory which is mostly inhabited temporarily, marked by unauthorised building, and threatened by various environmental and climate risks. Starting with an acknowledgement of the limits that traditional census and registry data have in detecting the use of territories characterised by seasonal use and informality, the paper analyses the variations in anthropic presence over multiple years and the incidence of permanent residents. The analyses were carried out using mobile positioning data extracted from the TIM Data Visual Insight (DVI) platform and refer to the period between September 2019 and September 2020. The results show evident heterogeneity among the different coastal settlements. In particular, there are substantial differences between the southern marine (San Cataldo, Torre Veneri, Frigole, Montegrappa) and northern ones (Torre Chianca, Spiaggiabella, Torre Rinalda), where the former show a greater presence of stable residents and a less pronounced seasonal fluctuation. These differences are fundamental for urban planning policies to determine in which areas the retreat of the building from the coast could cause more difficulties and inconveniences.